Displacing water from a low spot in a pipeline by a turbulent oil flow: Experiments and simulations. (23rd November 2022) - Yurishchev, A.; Ullmann, A.; Brauner, N.
Highlights: Prediction of the critical oil flow rate for avoiding water accumulation in pipelines. Critical oil velocity increases with the pipe diameter and reduces with oil viscosity. Surface tension and wall wetting significantly affect the oil–water flow dynamics. Numerical simulations are validated by lab scale experiments. 3D simulations are needed to represent the bends' effects on the oil–water dynamics. Abstract: Water may accumulate at low sections of oil transportation pipelines. Continuous removal of the water by the oil is essential to avoid possible damages to the pipeline and ensure proper oil flow. Lab-scale experiments were performed to determine the critical oil velocity that enables the removal of accumulated water by turbulent oil flow and to measure the water propagation velocity at supercritical oil velocities. Effects of the riser inclination, initial water volume, and oil flow rate on the oil–water flow phenomena were documented. The data obtained were compared with results of 2D and 3D numerical simulations. The oil viscosity and pipe diameter effects were tested via numerical simulations. More viscous oils have been found to reduce the critical oil velocity and increase water propagation velocities, however with a rather weak effect. The critical oil velocity increases with the pipe diameter and the water propagation velocity is reduced.